Kesiapan Pemerintah Desa Muaro Pijoan dalam Penerapan E-Govermentuntuk Meningkatkan Transparansi, Pelayanan Publik, dan Tata Kelola Pemerintahan Berbasis Digital - Reni Marchelia Siahaan; Yenny Yuniarti; Hendriyaldi Hendriyaldi (Ebisnis Manajemen, 2025)
This research is motivated by the gap between the support provided by the local government, which has provided the Village Information System (SID) facility to Muaro Pijoan Village, and the actual situation on the ground, which is not yet ready, both in terms of human resources, infrastructure, budget, and legal framework. As a result, the implementation of e-government in Muaro Pijoan Village has not been optimal, and public services are still largely performed manually. This research used a qualitative, descriptive approach. Data collection techniques included observation, interviews, documentation, and literature review. The results indicate that the readiness of the Muaro Pijoan Village Government remains low. In terms of technology utilization, the SID website only functions as a one-way information delivery service and does not yet support interactive public services. This study aims to determine the readiness of the Muaro Pijoan Village Government for e-government implementation and identify factors influencing this readiness.